Band of brothers - Richards, Mary; Hanks, Tom; Spielberg, Steven, 1946-; Acevedo, Kirk; Bailey, Eion; Cudlitz, Michael; Dye, Dale; Gomez, Rick; Grimes, Scott, 1971-; Hughes, Frank John; Lewis, Damian, 1971-; Livingston, Ron; et al. ([New York] : HBO Home Entertainment, 2014)
Tells the story of Easy Company, 506th Regiment of the 101st Airborne Division, U.S. Army, an elite rifle company that parachuted into France early on D-Day morning, fought in the Battle of the Bulge, captured Hitler's Eagle's Nest at Berchtesgaden, and suffered heavy casualties. Also includes a documentary about the soldiers in Easy Company
Disc 1. Part 1: Currahee / edited by Billy Fox ; director of photography, Joel J. Ransom ; teleplay by Erik Jendresen and Tom Hanks ; directed by Phil Alden Robinson ; Part 2: Day of days / edited by Frances Parker ; director of photography, Remi Adefarasin ; written by John Orloff ; directed by Richard Loncraine -- Disc 2. Part 3: Carentan / edited by Oral Norrie Ottey ; director of photography, Joel J. Ransom ; written by E. Max Frye ; directed by Mikael Salomon ; Part 4: Replacements / edited by Billy Fox ; director of photography, Joel J. Ransom ; written by Graham Yost and Bruce C. McKenna ; directed by David Nutter -- Disc 3. Part 5: Crossroads / edited by John Richards ; director of photography, Remi Adefarasin ; written by Erik Jendresen ; directed by Tom Hanks ; Part 6: Bastogne / edited by John Richards ; director of photography, Remi Adefarasin ; written by Bruce C. McKenna ; directed by David Leland -- Disc 4. Part 7: The breaking point / edited by Oral Norrie Ottey ; director of photography, Joel J. Ransom ; written by Graham Yost ; directed by David Frankel ; Part 8: The last patrol / edited by Frances Parker ; director of photography, Remi Adefarasin ; written by Erik Bork and Bruce C. McKenna ; directed by Tony To -- Disc 5. Part 9: Why we fight / edited by Frances Parker ; director of photography, Remi Adefarasin ; written by John Orloff ; directed by David Frankel Part 10: Bonus features: We stand alone together : the men of Easy Company / Home Box Office a Dreamworks/Playtone production in association with Cowen/Richter productions ; directed by Mark Cowen ; written by William Richter ; executive producers, Tom Hanks, Steven Spielberg ; produced by Mark Cowen, William Richter -- The making of Band of brothers -- Ron Livingston's video diaries -- Premiere in Normandy -- Who's who : the men of Easy Company -- Photo gallery.
Originally broadcast by HBO in 2001.
Based on the book by Stephen E. Ambrose.
Casting, Liberman/Patton ; costume designer, Anna Sheppard ; music by Michael Kamen ; production designed by Anthony Pratt ; co-executive producers, Stephen E. Ambrose, Gary Goetzman, Tony To.
Kirk Acevedo, Eion Bailey, Michael Cudlitz, Dale Dye, Rick Gomez, Scott Grimes, Frank John Hughes, Damian Lewis, Ron Livingston, James Madio, Neal McDonough, Rene L. Moreno, David Schwimmer, Richard Speight, Jr., Donnie Wahlberg, Matthew Settle, Douglas Spain, Rick Warden, Marc Warren, Shane Taylor, Dexter Fletcher, Colin Hanks, Ross McCall.
Not rated.
DVD; region 1; 16:9 widescreen aspect ratio.
Keywords: United States. -- Army. -- Parachute Infantry Regiment, 506th. -- Company E -- Drama; World War, 1939-1945 -- Airborne troops -- Drama; World War, 1939-1945 -- Campaigns -- Western Front -- Drama; War television programs; Television movies; War television programs; Historical television programs; Action and adventure television programs; Television mini-series.; Television adaptations; Video recordings for the hearing impaired